KONSEP DIRI BIDUAN DANGDUT ORGEN TUNGGAL DI KECAMATAN UKUI KABUPATEN PELALAWAN - Mega Anggriani; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The phenomenon of singular single organs is not only in the capital, but has penetrated to the area. Being a singular single singer is not an easy thing, given that singular singular singing is a rare job by society because it is considered low and full of freedom. There is still a great deal of opposition to work as singular singles singles are very influential on the concept of self-singular single orgen singer itself. This study aims to determine the physiological aspects,psychological aspects, psycho-sociological aspects, and psycho-ethical and moral aspects of the formation of self-concept single orgen singing in Kecamatan Ukui Pelalawan District.This research uses qualitative research method with descriptive approach. The subjects consisted of five single dangdut singer singers selected using the snowball technique. Data collection is done through in-depth interviews, observation and documentation. Data analysis techniques based on the Miles and Huberman cycles include data collection, data reduction,data organization, and conclusions.The results of this study indicate that the five informants of research have similarities, namely having a self-concept that tends to be positive. Physiologically they both looked positively at her appearance, and assumed that her physical being was no different from anyone else. Psychologically, the informant has a negative self-concept, because he sees himself as unhappy, pessimistic, unable to control himself and has various shortcomings. Psycho-sociologically, informants have a positive self-concept, although they work as singular singular singers, but they still have the confidence to interact with their social environment. And psycho-ethically the concept of singular single singleton singer also tends to be positive, because they still put forward ethical and moral values and do deeds.Keywords: Self-concept, Singular, Orgen Singing